AB0073 Measurement of the Anti-Inflammatory Molecule Glucocorticoid-Induced Leucine Zipper (GILZ) in Rheumatoid Arthritis Patients. (10th June 2014) - Eades, L.E.; Thiagarajah, A.S.; Gist, A.C.; Jones, S.A.; Harris, J.; Yang, Y.H.; Fan, H.; Foote, A.; Morand, E.F.; Leech, M.
Abstract : Background: Rheumatoid arthritis (RA) affects 1% of populations worldwide. Approximately 30% of RA patients receive treatment with glucocorticoids (GC), which cause significant toxicity (1). Glucocorticoid-induced leucine zipper (GILZ) is a GC-induced protein, which mediates many of the anti-inflammatory effects of GC, suggesting manipulation of GILZ as a potential therapeutic approach in RA (2, 3). However, little is known regarding GILZ expression in RA. Objectives: We aimed to detect GILZ in peripheral blood mononuclear cells (PBMC) of RA patients, examine the relationship between GILZ expression, disease activity and GC use, and assess GILZ expression relative to the expression of pro-inflammatory cytokines. Methods: Blood was collected from 86 RA patients and three control cohorts (23 healthy controls, 30 patients with fibromyalgia and 48 patients with depression). Clinical information regarding medications and disease activity was also obtained from RA patients. qRT-PCR was performed to quantify expression of GILZ, IL-6 and TNFα mRNA in PBMC. Enzyme-linked immunosorbent assay (ELISA) was performed to quantify serum IL-6 concentration. Results: GILZ expression was increased in RA patients compared with healthy controls ( p =0.002), patients with depression ( p =0.007) and patients with fibromyalgia ( p =0.046). GILZ expression correlated positively with disease activity (DAS28-ESR) in active RA ( p =0.025) and was significantly increased in patients taking prednisolone ( p =0.009). Compared to controls, GILZ:IL-6 ( p =0.026) and GILZ:TNFα ( p =0.005) ratios were significantly increased in RA. Conclusions: GILZ expression is increased in RA, and correlates with disease activity and GC use. Increased GILZ:cytokine ratios in RA suggest that GILZ expression may be increased in order to suppress inflammatory cytokines in vivo. These data support further research into the potentiation of GILZ as a possible steroid-sparing therapeutic approach in RA. References: O'Dell JR. Therapeutic strategies for rheumatoid arthritis. N Engl J Med. 2004 Jun 17;350(25):2591-602. Ayroldi E, Migliorati G, Bruscoli S, Marchetti C, Zollo O, Cannarile L, et al. Modulation of T-cell activation by the glucocorticoid-induced leucine zipper factor via inhibition of nuclear factor kappaB. Blood. 2001 Aug 1;98(3):743-53. Beaulieu E, Morand EF. Role of GILZ in immune regulation, glucocorticoid actions and rheumatoid arthritis. Nature reviews Rheumatology. 2011 Jun;7(6):340-8. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3176